2014
DOI: 10.12688/f1000research.5998.1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting self-management through adherence among heart failure patients discharged from rural hospitals: a study protocol

Abstract: Background Heart failure is one of the most prevalent chronic conditions in adults, leading to prolonged morbidity, repeated hospitalizations, and placing tremendous economic burden on the healthcare system. Heart failure patients discharged from rural hospitals, or primarily critical access hospitals, have higher 30-day readmission and mortality rates compared to patients discharged from urban hospitals. Self-management improves heart failure patients’ health outcomes and reduces re-hospitalizations, but adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…25 The study was approved by the university institutional review board and the hospital ethical committees. All subjects provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The study was approved by the university institutional review board and the hospital ethical committees. All subjects provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…cancer) which limited the patient's SM capacity. 25 With the exception of the Mini-Cog™ test, all other clinical diagnoses (e.g., NYHA, depression, cirrhosis, chronic renal failure, or terminal illness) were collected and confirmed from patients' medical records in hospital, primary care, and specialty clinics. We were unable to obtain the effect size from similar studies in comparable populations or from a pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…This secondary analysis used the baseline data from a randomized controlled trial titled “Patient AcTivated Care at Home (PATCH)” which was intended to examine the feasibility and efficacy of a 12-week home-based intervention to improve HF SM adherence(Young et al 2014). The study was approved by the University of Nebraska Medical Center Institutional Review Board (IRB PROTOCOL # 228-13-EP) and hospital ethical committees.…”
Section: Methodsmentioning
confidence: 99%
“…cancer) which limited the patient’s SM capacity. The details regarding sample and setting has been previously reported (Young et al 2014). To detect a medium effect correlation ( r = 0.28) using a two sided test, 5% significance level test (α=0.05) with power 80% power ( β =0.2), the required sample size is approximately 98 (n=98) (Hulley et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4]8,9 In addition, patients admitted to rural hospitals with diseases, such as congestive heart failure, are more likely to be readmitted to the hospital than patients in urban areas. 10,11 Studies have shown that rural areas have their own cultural patterns, which can influence their health care attitudes and health outcomes. [11][12][13][14] A series of patient interviews conducted in Australia and western states in the US showed that people were self-reliant out of necessity due to lack of access to health care or because of poor provider-patient relationships.…”
Section: Introductionmentioning
confidence: 99%